Emerging Antimicrobial-Resistant High-Risk Klebsiella pneumoniae Clones ST307 and ST147 - Peirano, Gisele; Chen, Liang; Kreiswirth, Barry N.; Pitout, Johann D. D. (Antimicrobial agents and chemotherapy, 2020)
There is an enormous global public health burden due to antimicrobial-resistant (AMR) Klebsiella pneumoniae high-risk clones. K. pneumoniae ST307 and ST147 are recent additions to the family of successful clones in the species. Both clones likely emerged in Europe during the early to mid-1990s and, in a relatively short time, became prominent global pathogens, spreading to all continents (with the exception of Antarctica). ST307 and ST147 consist of multiple clades/clusters and are associated with various carbapenemases (i. There is an enormous global public health burden due to antimicrobial-resistant (AMR) Klebsiella pneumoniae high-risk clones. K. pneumoniae ST307 and ST147 are recent additions to the family of successful clones in the species. Both clones likely emerged in Europe during the early to mid-1990s and, in a relatively short time, became prominent global pathogens, spreading to all continents (with the exception of Antarctica). ST307 and ST147 consist of multiple clades/clusters and are associated with various carbapenemases (i.e., KPCs, NDMs, OXA-48-like, and VIMs). ST307 is endemic in Italy, Colombia, the United States (Texas), and South Africa, while ST147 is endemic in India, Italy, Greece, and certain North African countries. Both clones have been introduced into regions of nonendemicity, leading to worldwide nosocomial outbreaks. Genomic studies showed ST307 and ST147 contain identical gyrA and parC mutations and likely obtained plasmids with bla CTX-M-15 during the early to mid-2000s, which aided in their global distribution. ST307 and ST147 then acquired plasmids with various carbapenemases during the late 2000s, establishing themselves as important AMR pathogens in certain regions. Both clones are likely underreported due to restricted detection methodologies. ST307 and ST147 have the ability to become major threats to public health due to their worldwide distribution, ability to cause serious infections, and association with AMR, including panresistance. The medical community at large, especially those concerned with antimicrobial resistance, should be aware of the looming threat posed by emerging AMR high-risk clones such as K. pneumoniae ST307 and ST147.